JAVANESE SPEECH HOST IN WEDDING IN THE SIDOARJO REGION - Suwito (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This study describes the Javanese language used by the presenters when bringing a wedding ceremony in the Sidoarjo area. Organizers have many variations of the language used at weddings with Javanese customs. The research method uses a qualitative research method approach where this research is in the Tambak Kemerakan village area, Krian sub-district, Sidoarjo district. The time of the research was carried out from May to July 2021. The data collection techniques in the study were in the form of documents, interviews and observations. The research instrument used a mobile phone and a list of questions to the presenters. The results of the study show that the use of language includes language variations, language variations based on lecturing functions, language variations in terms of formality using official language. Code switching in this study is an analysis of the language used when hosting weddings. And the occurrence of language code mixing in the form of Javanese krama alus switching to Indonesian and language interference in its morphological and phonological use.